Upaya Penanggulangan Konflik Antar Narapidana Di Lembaga Pemasyarakatan Narkotika Kelas II B Banyuasin - Yonani, Yonani (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
This study aims to explore the steps taken by the Banyuasin Class II B Narcotics Correctional Institution (Lapas) in overcoming conflicts that occur between prisoners. Conflict between prisoners is a serious problem that can disrupt stability and security within the prison. In this research, the author uses normative and empirical juridical approaches. The results show that the Correctional Institution has implemented various efforts to defuse conflicts, such as persuasive approaches and internal mediation, increased religious activities, skills training, strict supervision, as well as the formation of security squads involving prisoner leaders. However, despite these efforts, their effectiveness is still hampered by several challenges. Limited facilities, overcapacity, and lack of training for officers are some of the factors that hinder the success of these programs. Therefore, cross-sectoral cooperation is needed to create a safe, orderly, and conducive environment for all prisoners.